Connexin 43 Hemichannel Activity Promoted by Pro-Inflammatory Cytokines and High Glucose Alters Endothelial Cell Function - Sáez, Juan C.; Contreras-Duarte, Susana; Gómez, Gonzalo I.; Labra, Valeria C.; Santibañez, Cristian A.; Gajardo-Gómez, Rosario; Avendaño, Beatriz C.; Díaz, Esteban F.; Montero, Trinidad D.; Velarde, Victoria; Orellana, Juan A. (Frontiers in Immunology, 2018)
The present work was done to elucidate whether hemichannels of a cell line derived from endothelial cells are affected by proinflammatory conditions (high glucose and IL‐1β/TNF‐α) known to lead to vascular dysfunction. We used EAhy 926 cells treated with high glucose and IL‐1β/TNF‐α. The hemichannel activity was evaluated with the dye uptake method and was abrogated with selective inhibitors or knocking down of hemichannel protein subunits with siRNA. Western blot analysis, cell surface biotinylation and confocal microscopy were used to evaluate total and plasma membrane amounts of specific proteins and their cellular distribution, respectively. Changes in intracellular Ca2+ and NO signals were estimated by measuring FURA-2 and DAF-FM probes, respectively. High glucose concentration was found to elevate dye uptake, a response that was enhanced by IL-1β/TNF-α. High glucose plus IL-1β/TNF-α-induced dye uptake was abrogated by connexin 43 (Cx43) but not pannexin1 (Panx1) knock down. Furthermore, Cx43 hemichannel activity was associated with enhanced ATP release and activation of p38 MAPK, iNOS, COX2, PGE2 receptor EP1 and P2X7/P2Y1 receptors. Inhibition of the above pathways prevented completely the increase in Cx43 hemichannel activity of cells treated high glucose and IL‐1β/TNF‐α. Both synthetic and endogenous cannabinoids (CBs) also prevented the increment in Cx43 hemichannel opening, as well as the subsequent release of ATP and NO generation induced by pro-inflammatory conditions. The counteracting action of CBs also was extended to other endothelial alterations evoked by IL‐1β/TNF‐α and high glucose, including increased ATP-dependent Ca2+ dynamics and insulin-mediated NO production. Finally, inhibition of Cx43 hemichannels also prevented the ATP release from endothelial cells treated with IL‐1β/TNF‐α and high glucose. Therefore, we propose that reduction of hemichannel activity could represent a strategy against the activation of deleterious pathways that lead to endothelial dysfunction and possibly cell damage evoked by high glucose and pro-inflammatory conditions during cardiovascular diseases.